Fra la cattedrale e il bazar, punti di vista sull’informazione Geografica libera fra il 2007 e il 2013 - Giacomelli, Andrea (GEOmedia, 2010)
Geographic information: between a Cathedral and a bazar The article gives a high-level overview of three years of awareness raising on geographic free/Open Source software and information, conducted by the Italian OSGEO Chapter (GFOSS.it), and provides some outlook on the development of this sector in Italy.